2008
DOI: 10.1007/s11101-008-9090-8
|View full text |Cite
|
Sign up to set email alerts
|

Acetogenic anthraquinones: biosynthetic convergence and chemical evidence of enzymatic cooperation in nature

Abstract: Phenylanthraquinones belong to the quite rare class of fully unsymmetric biaryls, consisting of two different molecular portions, an anthraquinone part, chrysophanol, and a phenyl part, 2,4-dihydroxy-6-methoxyacetophenone, linked together by phenol-oxidative coupling. The biosynthesis of these two moieties, from eight and four acetate units, respectively, bears some unique features: Chrysophanol is the first example of an acetogenic natural product that is, in an organismspecific manner, formed via more than o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…In plants, insects, and fungi, the polyketide chain is cyclized through “F” mode in which the first ring of polyketide is built by two C2 units (acetyl CoA), whereas in “S” mode, it is formed by three C2 units [22]. Bringmann and Irmer [81] designed a study to distinguish four possible folding patterns: the F and S modes, which were already known and the hypothetical S’ and F’ modes, which were never explored (Figure 1). Their study was accomplished by feeding 13 C-labeled sodium acetate as the precursor of acetyl-CoA to different model organisms, such as Nocardia strain (bacterium), Galeruca tanaceti larvae (insect), callus culture of the torch lily, Kniphofia uvaria (plants), and Drechslera catenaria (fungi).…”
Section: Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…In plants, insects, and fungi, the polyketide chain is cyclized through “F” mode in which the first ring of polyketide is built by two C2 units (acetyl CoA), whereas in “S” mode, it is formed by three C2 units [22]. Bringmann and Irmer [81] designed a study to distinguish four possible folding patterns: the F and S modes, which were already known and the hypothetical S’ and F’ modes, which were never explored (Figure 1). Their study was accomplished by feeding 13 C-labeled sodium acetate as the precursor of acetyl-CoA to different model organisms, such as Nocardia strain (bacterium), Galeruca tanaceti larvae (insect), callus culture of the torch lily, Kniphofia uvaria (plants), and Drechslera catenaria (fungi).…”
Section: Biosynthesismentioning
confidence: 99%
“…This interaction might be due to the inter-acetate couplings, usually not found in the S mode. There is a further need to certify the F’ mode that is theoretically possible [81]. However, the F and S modes offer different intermediates but ultimately produce the same chemical structure through an aldol reaction, followed by decarboxylation.…”
Section: Biosynthesismentioning
confidence: 99%
“…It is not known whether the Tomopteris synthesizes aloe‐emodin or acquires it elsewhere, perhaps through its diet or from a symbiont. Many anthraquinones are biosynthesized through a convergent mechanism using polyketide synthases , a mechanism that is conserved across prokaryotes, fungi and plants, thus any of those modes of acquisition may be possible. A dietary link from land plants would be preposterous; however, there are other cases of anthraquinones from marine organisms, including a marine fungus that lives commensally with a green alga and appears to produce several anthraquinones and an isomer of aloe‐emodin .…”
Section: Discussionmentioning
confidence: 99%
“…These basic aromatic structures could be formed convergently by divergent polyketide biosynthesis systems. Although recent reviews covered convergent biosynthetic strategies in anthraquinonoid biosynthesis revealed by feeding experiments, [183][184][185] here we deal with aromatic polyketides for which the information about the PKSs responsible is available on genetic and/or enzyme levels.…”
Section: Convergent Strategies In Aromatic Polyketide Biosynthesis 51...mentioning
confidence: 99%